2004
DOI: 10.1176/appi.ajp.161.3.490
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Broadband Noise, Working Memory, and Genetic Risk for Schizophrenia

Abstract: Frontal lobe-related cognitive function depends on the ability to synchronize cortical pyramidal neurons, which is in part genetically controlled. Increased prefrontal "noise" is an intermediate phenotype related to genetic susceptibility for schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
149
7
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(185 citation statements)
references
References 102 publications
(109 reference statements)
23
149
7
6
Order By: Relevance
“…The issue of baseline gamma differences is important, given that most studies examining group differences in post-stimulus activity employ some form of baseline correction (Urbach and Kutas, 2006). Two very large studies reported elevated prestimulus gamma power in schizophrenia patients during auditory paradigms (Winterer et al, 2004;Hong et al, 2008), in accordance with our previous data (Turetsky and Siegel, 2007) (Figure 4). Two smaller studies found no group differences in pre-stimulus gamma band responses, but did report elevated baseline beta power in schizophrenia (Brockhaus-Dumke et al, 2008).…”
Section: Findings In Disease Resting State Network and Gamma Oscillatsupporting
confidence: 87%
See 2 more Smart Citations
“…The issue of baseline gamma differences is important, given that most studies examining group differences in post-stimulus activity employ some form of baseline correction (Urbach and Kutas, 2006). Two very large studies reported elevated prestimulus gamma power in schizophrenia patients during auditory paradigms (Winterer et al, 2004;Hong et al, 2008), in accordance with our previous data (Turetsky and Siegel, 2007) (Figure 4). Two smaller studies found no group differences in pre-stimulus gamma band responses, but did report elevated baseline beta power in schizophrenia (Brockhaus-Dumke et al, 2008).…”
Section: Findings In Disease Resting State Network and Gamma Oscillatsupporting
confidence: 87%
“…However, three did report elevations in high beta (20-30 Hz) power, interpreted as reflecting "cortical noise" (Kissler et al, 2000;Krishnan et al, 2005;Brockhaus-Dumke et al, 2008), although another did not (Miyauchi et al, 1990). A larger EEG study observed increased 20-50 Hz power in schizophrenia subjects and their relatives (Venables et al, 2009) and another group found broad band increases of baseline activity at all frequencies (Winterer et al, 2004). Although a similar MEG study employing sourcespace projections found opposite results (Rutter et al, 2009).…”
Section: Findings In Disease Resting State Network and Gamma Oscillatmentioning
confidence: 96%
See 1 more Smart Citation
“…Working memory tasks invoke the dorsolateral prefrontal cortex (DLPFC), a brain region known to be disrupted both structurally and functionally in patients with schizophrenia. 40,41 A recent analysis of all allelic variants of the HEP1 to HEP3 haplotypes in relation to neurocognitive functions and gray matter volume in a sample of Finnish twins concordant and discordant for schizophrenia observed association of a rare allele of a haplotype consisting of the SNPs combined from HEP2 and HEP3 (HEP2/HEP3) with increased risk for schizophrenia, decreased gray matter in prefrontal cortex, and impaired visuospatial working memory functioning (Cannon, et al, in press) (Figure 1). The findings across these two independent samples thus provide some degree of convergence in implicating the TRAX/ DISC loci as associated with visuospatial working memory and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous observations suggest an abnormal function of this cortical area in schizophrenia (Elvevag and Goldberg, 2000;Goldman-Rakic, 1994;Lewis and Anderson, 1995;Uhlhaas and Singer, 2010;Uhlhaas and Singer, 2006;Winterer et al, 2004). In particular, anatomical, cellular, and neurochemical alterations have been reported in the frontal lobe of patients with schizophrenia (Harrison, 1999;Lewis and Lieberman, 2000;Lewis et al, 2005;Selemon and Goldman-Rakic, 1999).…”
Section: Introductionmentioning
confidence: 99%